Kinerja Penyuluh Pertanian Di Kecamatan Bolangitang Barat Kabupaten Bolaang Mongondow Utara - Bangko, Abdul Rafik; Pangemanan, Lyndon Reindhart Jacob; Tangkere, Ellen Grace (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2024)
This study aims to determine the performance of agricultural extension workers in West Bolangitan District, North Bolaang Mongondow Regency. This research was conducted from February - March 2023. This study used primary data and secondary data. Primary data was obtained directly from interviews with farmers using a questionnaire and secondary data obtained by the local government. Method of collecting data from farmers in West Bolaang Mongondow District, North Bolaang Mongondow Regency. Seeing the existing population of the 103 farmer groups in West Bolangitang District, purposive sampling was taken from the 103 farmer groups. The number of samples taken was 75 respondents. The results of the research and discussion show that the performance of agricultural extension workers in West Bolangitang District, North Bolaang Mongondow Regency, seen from 8 indicators, gets a total score of 1095 with fairly good criteria.